Интродукция лиан и их использование на юго-востоке Украины - Костырко, Д.Р. (Промышленная ботаника, 2004)
The results of long-term (1966-2003) introductional experiment on the trial of ligneous and herbaceous lianas under conditions of Donbass have been summed up. A collection of lianas containing, as per data in effect on 01.01.2004, 138 species, varieties and forms of lianas from 38 genera and 22 families, has been created. Growth and development peculiarities (phenology, florescence, fructification, shoots formation) have been studied. Some anatomic-and-morphologic peculiarities (leaf anatomic texture, root systems, buds integument) determining successfulness of introduction into new conditions, drought resistance and winter hardyness have been investigated. The assortment of the most perspective liana species – ligneous (31 species), perennial herbaceous (8 species) and annual (22 species) lianas, – has been selected. Four basic age periods in ligneous lianas development under introduction to Donbass have been distinguished. A spectrum of the greatest ornamental effect enabling to select on its basis the desirable assortment in each particular case, has been compiled. A module system of constructing an exposition “Garden of lianas” has been developed, new forms of Ampelopsis aconitifolia f. auranticarpina Kostyrko and Clematis manschuriensis f. pubescens Kost. et Gorl. have been singled out and described.